Advancements in Material Design and Motion Control: Integrating Additive Manufacturing, Fused Deposition Modeling, and Precision Systems in Modern Applications - Aishwarya Tiwari (International Journal of Electro-Mechanics and Material Behaviour, 2024)
The interaction between material design, mechanical properties, and advanced motion control systems is vital in a range of engineering domains, including robotics, electronics, and manufacturing. This article examines two key areas: the mechanical properties and design of cutting-edge materials, focusing on composites, polymers, ceramics, and fibers, and the integration of advanced motion control systems in hand-held electronic and photographic devices. The first section delves into the mechanical behavior of various materials, with an emphasis on composite systems such as polymer matrix composites, and the application of additive manufacturing methods like fused deposition modeling in material fabrication. The second section explores recent advancements in motion control systems, especially for hand-held devices used in digital imaging, photography, and electronic displays. Topics covered include position and process control, which are essential for achieving high precision and efficiency across different technological applications. This article aims to showcase the synergy between material design and motion control, highlighting how their combined potential is driving innovations in manufacturing, electronics, and digital technologies.
Keywords: Additive manufacturing; Fused Deposition Modeling (FDM); composite materials; material design; motion control systems